2010
DOI: 10.1007/s00414-010-0525-6
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art of bone marrow analysis in forensic toxicology: a review

Abstract: Although blood is the reference medium in the field of forensic toxicology, alternative matrices are required in case of limited, unavailable or unusable blood samples. The present review investigated the suitability of bone marrow (BM) as an alternative matrix to characterize xenobiotic consumption and its influence on the occurrence of death. Basic data on BM physiology are reported in order to highlight the specificities of this matrix and their analytical and toxicokinetic consequences. A review of case re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 67 publications
0
30
0
1
Order By: Relevance
“…Bone marrow: Collect all available for a 10 mL plastic container with screw cap (without preservative); useful in advanced stages of putrefaction since it is protected by bones; high degree of vascularity and lipid content (may accumulate lipophilic xenobiotics); different xenobiotic concentrations are registered in the marrow obtained from the same or different bones [ 24 ]; in xenobiotic distributions are possible [ 20 ]; the label should detail the sampling site; typically, the ribs are cut approximately 5 cm far from its distal end (i.e. near the medioclavicular line) where it is ossified.…”
Section: Procedures For Collectionmentioning
confidence: 99%
“…Bone marrow: Collect all available for a 10 mL plastic container with screw cap (without preservative); useful in advanced stages of putrefaction since it is protected by bones; high degree of vascularity and lipid content (may accumulate lipophilic xenobiotics); different xenobiotic concentrations are registered in the marrow obtained from the same or different bones [ 24 ]; in xenobiotic distributions are possible [ 20 ]; the label should detail the sampling site; typically, the ribs are cut approximately 5 cm far from its distal end (i.e. near the medioclavicular line) where it is ossified.…”
Section: Procedures For Collectionmentioning
confidence: 99%
“…For diazepam, it is known to accumulate in bone marrow and the clearance appears to be slower in bone marrow than in blood. 33 In the study of Imfeld et al, colchicine was still present in the blood when bone concentrations were determined. 30…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Gorczynski et al , midazolam showed to be present in bone using an enzyme‐linked immunosorbent assay (ELISA), although midazolam was also still detectable in serum. For diazepam, it is known to accumulate in bone marrow and the clearance appears to be slower in bone marrow than in blood . In the study of Imfeld et al , colchicine was still present in the blood when bone concentrations were determined .…”
Section: Discussionmentioning
confidence: 99%
“…Stability of drugs in the bone marrow has predominantly been examined in animal models. Methamphetamine was found to be stable over 2 years when bone samples were stored in a dry environment, whereas opioid levels showed a substantial decrease over a few weeks in buried bones (Cartiser et al 2011). …”
Section: Stability Of Drugs and Formation Of Artefacts In Postmortem mentioning
confidence: 99%